PENGEMBANGAN APLIKASI TEXT TO SPEECH DALAM PEMBUATAN KAMUS UNTUK TUNANETRA - Eka Damayanthi, Luh Putu (Universitas Pendidikan Ganesha, 2014)
Nowadays, understanding and mastery of English language is very important foreveryone, not least for those who have limitations, such as people with visual impairment. Generally, people learn English, by using dictionary. But for people with visualimpairment, are not allowed to use the dictionary, just like a normal person in general.They require specialized dictionaries, for example dictionaries that use Braille format. The using of dictionaries in Braille format even this could not be done optimally, becauseto find the translation of a word, they must find the word manually, such as by reading with your finger.By the advancement of science and technology, especially in the field ofcomputerization, dictionary application media was made to help people with visual impairment in performing the translation of a word by using the senses of hearing. Inmaking this application, the hardware, which used is a desktop or laptop computercompleted with the speakers, while its software consists of modules Borland Delphi and TTS (Text To Speech). The application of the dictionary that created tailored to the characteristics of people with visual impairment, such as on interface design created the shortcuts or special keys on the keyboard to perform a particular function. Input given tothe system, namely in the form of text, followed by the TTS module will be converted to text utterance.This dictionary application is expected to provide facilities for persons with visualimpairment in learning English language, without need high intensity to do the translation of a word, so that the productivity of learning, both at school and at home can beimproved continously.